2014
DOI: 10.1111/1750-3841.12345
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Thermal Sterilization: Food Safety and Food Quality of Baby Food Puree

Abstract: The benefits that high-pressure thermal sterilization offers as an emerging technology could be used to produce a better overall food quality. Due to shorter dwell times and lower thermal load applied to the product in comparison to the thermal retorting, lower numbers and quantities of unwanted food processing contaminants (FPCs), for example, furan, acrylamide, HMF, and MCPD-esters could be formed. Two spore strains were used to test the technique; Geobacillus stearothermophilus and Bacillus amyloliquefacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 44 publications
(84 reference statements)
3
38
0
Order By: Relevance
“…The target modified by heat activation leading to increased 550-MPa HP germination is not clear, but two possibilities are (a) the spore IM, where many germination proteins, including the SpoVA proteins comprising the Ca-DPA channel thought to be activated by HPs of Ն500 MPa, are located (1,2,19,24,43), and (b) one or more of the SpoVA proteins themselves. (v) Finally, the observation that heat activation also markedly stimulated HP germination of B. amyloliquefaciens spores may have applied implications, since HP germination and subsequent heat inactivation of less resistant germinated spores can minimize spore loads in shelfstable foods (24)(25)(26)(27), and B. amyloliquefaciens spores have been proposed for use as a surrogate for C. botulinum spores in analysis of regimens for spore inactivation by HP (28,29). HP treatment for the commercial sterilization of foodstuffs is almost always carried out at temperatures much higher than the 50°C used in our study, and even with short processing times, temperatures and HPs may be sufficient to cause significant spore heat activation during the HP treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The target modified by heat activation leading to increased 550-MPa HP germination is not clear, but two possibilities are (a) the spore IM, where many germination proteins, including the SpoVA proteins comprising the Ca-DPA channel thought to be activated by HPs of Ն500 MPa, are located (1,2,19,24,43), and (b) one or more of the SpoVA proteins themselves. (v) Finally, the observation that heat activation also markedly stimulated HP germination of B. amyloliquefaciens spores may have applied implications, since HP germination and subsequent heat inactivation of less resistant germinated spores can minimize spore loads in shelfstable foods (24)(25)(26)(27), and B. amyloliquefaciens spores have been proposed for use as a surrogate for C. botulinum spores in analysis of regimens for spore inactivation by HP (28,29). HP treatment for the commercial sterilization of foodstuffs is almost always carried out at temperatures much higher than the 50°C used in our study, and even with short processing times, temperatures and HPs may be sufficient to cause significant spore heat activation during the HP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, methods to increase spore germination by HP are of significant applied interest. To determine if heat activation might affect the HP germination of spores of applied interest, we used spores of B. amyloliquefaciens, which have been suggested as a good surrogate for spores of C. botulinum in analyzing the efficacy of regimens for spore inactivation by HP (28,29). Strikingly, heat activation for 4 h at 70°C markedly increased the germination of B. amyloliquefaciens spores at HPs of both 150 and 550 MPa (Fig.…”
Section: Fig 4 Effects Of Heat Activation On Germination Of Spores Wimentioning
confidence: 99%
See 1 more Smart Citation
“…High pressure thermal (HPT) processing uses the synergistic effect of high hydrostatic pressure (HHP) and temperature to inactivate microorganisms and presents a promising tool to increase food safety and durability, while quality characteristics are less affected as compared to conventional retorting. [8,9] To determine the effectiveness of a preservation process, a specific food is commonly inoculated with at least 10 6 spores (stipulated reduction factor for C. botulinum when other preservative factors are involved; [10] up to 10 12 for heat treatments of canned, low-acid foods) followed by the demonstration that no growth and toxin formation is initiated during the intended product shelf life at normal and abusive storage conditions. Independently from food matrix-related effects on spore inactivation, we previously showed that HPT could be generally used to effectively reduce C. botulinum type E viable spore counts by several log cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a benchmark dose lower confidence limit (BMDL 10 ) of 0.96 mg/kg bw per day, the Joint FAO/WHO Expert Committee on Food Additives (2011) has indicated a human health concern for furan and consequently, actions should be taken to minimize exposure to an acceptable level. To date, research for furan mitigation has mostly been targeted at the levels of food production (Fan and Mastovska, 2006;Sevenich et al, 2014;Palmers et al, 2014) and consumption (Hasnip et al, 2006;Roberts et al, 2008;Kim et al, 2009), both with varying success. The reduction of furan concentrations was found to be challenging, because of the variety of possible furan precursors and the microbial safety standards to be guaranteed.…”
Section: Introductionmentioning
confidence: 99%